Bio-based cobalt salt with resin characteristics and preparation method thereof

By using plant -based acid and cobalt source and other raw materials such as phenol -containing hydroxyl -based structures, prepare biological cobalt salt with resin characteristics, solve the environmental protection and performance problems of existing rubber cobalt salt adhesives during vulcanization, and achieve better. Rubber performance and environmental protection.

CN119331536APending Publication Date: 2025-01-21JIANGYIN SANLIANG CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411321615.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing rubber cobalt salt adhesives have environmental problems during vulcanization, complex process, high cost, and pollution to the environment and human body caused by formaldehyde release.

Method used

The first plant-based acid and the second plant-based acid containing a phenolic hydroxyl structure are used as raw materials, combined with cobalt sources, solvents and plant auxiliaries, and a bio-based cobalt salt with resin properties is prepared through specific preparation steps.

Benefits of technology

This biological cobalt salt material shows better dispersal compatibility when combining rubber, forms a network of networking, improves the physical properties of rubber, and has the characteristics of heat -resistant oxygen resistance, humidity resistance, saline resistance and slowing metal rust.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a bio-based cobalt salt with resin characteristics and a preparation method thereof, and relates to the technical field of rubber products. The invention discloses a bio-based cobalt salt with resin characteristics. The bio-based cobalt salt is prepared from the following raw material components in parts by weight: 15-30 parts of first plant-based acid, 10-25 parts of second plant-based acid, 15-35 parts of a cobalt source, 25-35 parts of a solvent and 5-10 parts of a plant additive, the first plant-based acid contains a phenolic hydroxyl structure; vanillic acid is adopted as the first plant-based acid; cumaric acid is adopted as the second plant-based acid; the cobalt source adopts industrial cobalt hydroxide with the cobalt content of more than or equal to 61.5%; the solvent is dimethyl carbonate; the plant auxiliary agent adopts plant microcrystalline cellulose, and the purity of the plant microcrystalline cellulose is greater than or equal to 99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber products, and in particular to a bio-based cobalt salt with resin properties and a preparation method thereof. Background Art

[0002] Rubber cobalt salt adhesive is mainly used for bonding galvanized and brass-plated metal skeletons to rubber. Before the rubber containing cobalt salt is vulcanized, there is only simple contact between the rubber and the brass coating, but once vulcanized, a new material layer will be formed between the two, especially a metal sulfide layer, such as cuprous sulfide layer (CuxS) and zinc sulfide layer (ZnS). The bonding structure layer formed by the rubber cobalt salt adhesive is mainly composed of cuprous sulfide, which has the activity of continuing reaction and can form a chemical bond (Cux-S-Sy-rub) through sulfur bridges to achieve bonding between rubber and brass coating. In this process, Co in the organic cobalt salt 2+ Cobalt ions only promote the formation of active cuprous sulfide.

[0003] However, the cobalt borate and cobalt neodecanoate in the prior art are mostly mixed carboxylic acids mainly composed of medium- and short-chain acids, which have strong acidity and affect the aging resistance of steel cords. In addition, during the synthesis process, Co is easily generated, which is not conducive to rubber adhesion. 3+ In addition, most synthesis technologies use non-environmentally friendly (benzene) solvents, which lead to increased energy consumption, harsh storage conditions, and potential safety hazards. Used organic solvents need to be recycled, which not only consumes energy, but also cannot be fully recycled, and some reagents are still discharged into the environment.

[0004] At present, the bonding system formula of major tire companies mainly uses resorcinol formaldehyde resin and HMMM with organic acid cobalt salt to form a meta-formaldehyde-white-cobalt bonding system. Although the anti-aging performance is good, the process is complicated, the cost is high, and the release of formaldehyde will cause pollution to the environment and human body. Therefore, it is urgent to study an eco-friendly resin cobalt salt that has both resin network characteristics under vulcanization conditions, using plant acid as raw material to achieve renewable and sustainable development, and adding plant additives to give full play to the adhesion-promoting effect of the resin cobalt salt and provide excellent anti-aging and physical properties.

[0005] Therefore, the present invention prepares a bio-based cobalt salt with resin properties. Summary of the invention

[0006] In order to solve the existing technical problems, the present invention discloses a bio-based cobalt salt with resin properties. The raw material components include, by weight: 15 to 30 parts of a first plant-based acid, 10 to 25 parts of a second plant-based acid, 15 to 35 parts of a cobalt source, 25 to 35 parts of a solvent, and 5 to 10 parts of a plant additive; the first plant-based acid contains a phenolic hydroxyl structure.

[0007] Furthermore, the first plant-based acid is vanillic acid, and the purity of the vanillic acid is ≥99%.

[0008] Furthermore, the second plant-based acid is coumaric acid, and the purity of coumaric acid is ≥99%.

[0009] Furthermore, the cobalt source is industrial cobalt hydroxide with a cobalt content of ≥61.5%.

[0010] Furthermore, the solvent is dimethyl carbonate.

[0011] Furthermore, the plant adjuvant is plant microcrystalline cellulose, and the purity of the plant microcrystalline cellulose is ≥99%.

[0012] The present invention also provides a method for preparing a bio-based cobalt salt having resin properties, comprising the following preparation steps: (1) Weighing and setting aside the raw material components according to the raw material components and weight proportions of the bio-based cobalt salt with resin properties according to any one of claims 1 to 6; (2) The solvent, the first plant-based acid, and the second plant-based acid weighed in step (1) are added to the reactor in sequence, followed by a first stage of heating and stirring, followed by adding a cobalt source and stirring for 5 minutes, followed by a second stage of heating, followed by reflux at a temperature of 1 to 1.5 hours; then a third stage of heating is performed, followed by distillation under negative pressure for 1 to 3 hours, followed by adding a plant adjuvant, stirring for 0.5 hours, and then discharging and granulating to obtain a bio-based cobalt salt having resin properties.

[0013] Furthermore, the first stage of heating is to raise the temperature to 100-120°C.

[0014] Furthermore, the second stage of heating is to raise the temperature to 150-160°C.

[0015] Furthermore, the three-stage temperature increase is to increase the temperature to 200-240°C; the negative pressure is ≤-0.085MPa.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a first plant-based acid and a second plant-based acid containing a phenolic hydroxyl structure as main raw materials to prepare a bio-based cobalt salt having resin properties. The material not only reduces dependence on petroleum-based organic acids, but also exhibits better dispersion compatibility when combined with natural rubber. It also gives the bio-based cobalt salt resin bonding properties. Its weak acidity enables it to exchange with the methylene donor in the rubber to form a cross-linked network, thereby increasing the cross-linking density and modulus of the rubber, enhancing the adhesion between the rubber and the skeleton material, and further improving the overall physical properties. At the same time, the rubber added with the bio-based cobalt salt has the characteristics of heat and oxygen resistance, moisture and heat resistance, salt water resistance, and slowing down metal corrosion.

[0017] (2) The present invention uses vanillic acid as the first plant-based acid. Vanillic acid is a natural organic acid that can generate salts by reacting with alkali. It comes from the plant kingdom and belongs to the same cinnamic acid derivative as vanillin. It is widely present in various plants and their essential oils such as vanilla beans, vanilla pods, Peruvian balsam, benzoin and Javanese oil in nature. Vanillic acid contains phenolic hydroxyl groups and can combine with methylene donors to form a cross-linked resin structure. Vanillic acid has good thermal stability, and its synthetic product has excellent antioxidant properties and can scavenge oxidative free radicals. Therefore, the bio-based cobalt salt synthesized using vanillic acid can better control Co in the production process. 3+ ion generation, reducing Co 3+ It affects the bonding performance between rubber and skeleton materials and reduces the impact of free radicals during rubber aging; in addition, the phenolic hydroxyl group of vanillic acid can be combined with the methylene donor to generate a resin functional compound with a cross-linked structure, thereby providing better strength and performance improvement for vulcanized rubber.

[0018] (3) The second plant-based acid of the present invention is coumaric acid, which is a natural compound extracted from the seeds of leguminous plants. Coumaric acid can undergo ion exchange reactions with metal ions, and because it can form resonance-stabilized phenolic free radicals, its synthetic compound has good antioxidant activity. Coumaric acid is the most important type of hydroxycinnamic acid compounds and is widely present in plants in nature, especially in the stems of grasses and leguminous plants. As a major component of lignocellulose, coumaric acid can not only improve the strength of rubber, but also has significant antioxidant effects. The antioxidant effect of coumaric acid is reflected in its ability to inhibit free radical activity, including DPPH free radical scavenging ability, reducing power and hydrogen peroxide scavenging ability. Since coumaric acid contains a phenolic group, it mainly reacts with free radicals through the phenolic hydroxyl group to generate relatively stable semiquinone free radicals, thereby terminating the chain reaction of free radicals and playing a positive role in the rubber aging process.

[0019] (4) The solvent selected in the present invention is dimethyl carbonate (DMC), which has excellent solubility, a narrow melting point and boiling point range, a large surface tension, a low viscosity, a small dielectric constant, and a high evaporation temperature and a fast evaporation rate. DMC is not only low in toxicity, but also has the characteristics of a high flash point, a low vapor pressure and a high lower explosion limit in the air. DMC can be recycled and reused to save costs, and can replace benzene solvents to reduce production problems in terms of environmental protection and safety. It is a green solvent that is both clean and safe.

[0020] (5) The present invention adds plant microcrystalline cellulose during the preparation process; plant microcrystalline cellulose is widely present in plants, animals and microorganisms, especially in textiles and paper made of raw materials such as straw, bagasse, wood and cotton; it has the advantages of wide source, low cost, renewable, degradable, environmentally friendly and low density; adding plant microcrystalline cellulose can improve the mechanical properties and crosslinking density of rubber, enhance its water absorption, barrier properties, conductivity and dynamic mechanical properties, and enhance the water aging resistance and vulcanization adhesion of bio-based cobalt salt; since its surface contains many hydrophilic groups, a small amount of addition can effectively enhance the moisture and heat aging resistance of bio-based cobalt salt and the tensile strength of rubber; by extracting plant microcrystalline cellulose from cotton, rice straw, wheat straw or wood pulp as a plant adjuvant, the tensile strength of rubber products can be significantly improved, so that this bio-based cobalt salt can effectively improve the initial and post-aging adhesion of rubber.

[0021] (6) Each glucose unit of the plant microcrystalline cellulose in the present invention contains three hydroxyl groups, which makes it easy for the cellulose molecular chain to form intramolecular and intermolecular hydrogen bonds, thereby having high rigidity and tending to aggregate to form an ordered crystalline structure. These crystalline structures give cellulose fibrils high strength and excellent mechanical properties, but also make it difficult to dissolve in general organic solvents, which makes the plant microcrystalline cellulose poorly dispersible in bio-based cobalt salts with resin properties, further affecting its dispersibility in rubber. To this end, the present application adds a first plant-based acid, coumaric acid, and a second plant-based acid, vanillic acid, which can penetrate into the interior of the microcrystalline cellulose particles and graft therewith, thereby destroying the crystalline structure and intermolecular hydrogen bonds of the cellulose molecules, while reducing the polarity of the microcrystalline cellulose to improve its compatibility with non-polar or low-polar rubbers, and enhance the bonding between the plant microcrystalline cellulose and the rubber, thereby significantly improving the performance of the rubber. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with examples, but the following examples should not be construed as limiting the present invention.

[0023] Some of the raw materials of the embodiments of the present invention and the comparative examples are as follows: The vanillic acid is commercially available industrial vanillic acid with a purity of ≥99%; The coumaric acid is commercially available industrial coumaric acid with a purity of ≥99%; The cobalt hydroxide is commercially available industrial cobalt hydroxide, wherein the cobalt content is ≥ 61.5%; The dimethyl carbonate is commercially available industrial dimethyl carbonate with a purity of ≥99%; The plant microcrystalline cellulose is commercially available industrial plant microcrystalline cellulose, with an effective ingredient of ≥99%; The mass fraction of cobalt in the cobalt stearate salt is 9.5%; The cobalt mass fraction of the boroacylated cobalt salt is 22%; The mass fraction of cobalt in the neodecanoate cobalt salt is 20.5%. Example 1

[0024] A method for preparing a bio-based cobalt salt having resin properties comprises the following preparation steps: (1) Weigh and set aside the following raw material components according to their weight proportions: 18 parts of vanillic acid, 20 parts of coumaric acid, 15 parts of cobalt hydroxide, 25 parts of dimethyl carbonate, and 5 parts of plant microcrystalline cellulose; (2) The dimethyl carbonate, vanillic acid and coumaric acid weighed in step (1) are added to the reactor in sequence, and then the temperature is raised to 110° C. and stirred evenly at the temperature. Then, cobalt hydroxide is added, stirred for 5 minutes, and then the temperature is raised to 150° C. and refluxed at the temperature for 1 hour. Then, the temperature is raised to 220° C. and distilled at a negative pressure of -0.085 MPa for 2 hours. Then, plant microcrystalline cellulose is added, stirred for 0.5 hours, and then the material is discharged and granulated to obtain a bio-based cobalt salt with resin properties. The reaction product contains 16.12% cobalt, has a melting point of 105° C., and is a red-purple solid in appearance. Example 2

[0025] A method for preparing a bio-based cobalt salt having resin properties comprises the following preparation steps: (1) Weigh and set aside the following raw material components according to their weight proportions: 18 parts of vanillic acid, 25 parts of coumaric acid, 18 parts of cobalt hydroxide, 30 parts of dimethyl carbonate, and 5 parts of plant microcrystalline cellulose; (2) The dimethyl carbonate, vanillic acid and coumaric acid weighed in step (1) are added to the reactor in sequence, and then the temperature is raised to 110° C. and stirred evenly at the temperature. Then, cobalt hydroxide is added, stirred for 5 minutes, and then the temperature is raised to 150° C. and refluxed at the temperature for 1 hour. The temperature is then raised to 225° C. and distilled at a negative pressure of -0.085 MPa for 1 hour. Then, plant microcrystalline cellulose is added, stirred for 0.5 hours, and then the material is discharged and granulated to obtain a bio-based cobalt salt with resin properties. The reaction product contains 16.03% cobalt, has a melting point of 101° C., and is a red-purple solid in appearance. Example 3

[0026] A method for preparing a bio-based cobalt salt having resin properties comprises the following preparation steps: (1) Weigh and set aside the following raw material components according to their weight proportions: 30 parts of vanillic acid, 25 parts of coumaric acid, 25 parts of cobalt hydroxide, 35 parts of dimethyl carbonate, and 10 parts of plant microcrystalline cellulose; (2) The dimethyl carbonate, vanillic acid and coumaric acid weighed in step (1) are added to the reactor in sequence, and then the temperature is raised to 120° C. and stirred evenly at the temperature. Then, cobalt hydroxide is added and stirred for 5 minutes, and then the temperature is raised to 160° C. and refluxed at the temperature for 1 hour. Then, the temperature is raised to 230° C. and distilled for 3 hours under a negative pressure of -0.085 MPa. Then, plant microcrystalline cellulose is added, stirred for 0.5 hours, and then the material is discharged and granulated to obtain a bio-based cobalt salt with resin properties. The reaction product contains 16.18% cobalt, has a melting point of 110° C., and is a red-purple solid in appearance.

[0027] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that only dimethyl carbonate, coumaric acid, cobalt hydroxide and plant microcrystalline cellulose are used to prepare the bio-based cobalt salt with resin properties, and the remaining steps are the same as those in Example 2.

[0028] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that only dimethyl carbonate, vanillic acid, cobalt hydroxide and plant microcrystalline cellulose are used to prepare the bio-based cobalt salt with resin properties, and the remaining steps are the same as those in Example 2.

[0029] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that only dimethyl carbonate, vanillic acid, coumaric acid and cobalt hydroxide are used to prepare the bio-based cobalt salt with resin properties, and the remaining steps are the same as those in Example 2.

[0030] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that only dimethyl carbonate, cobalt hydroxide and plant microcrystalline cellulose are used to prepare the bio-based cobalt salt with resin properties, and the remaining steps are the same as those in Example 2.

[0031] Table 1 below shows the components of the rubber materials prepared using the bio-based cobalt salts with resin properties obtained in Examples 1 to 3 and Comparative Examples 1 to 4 of the present invention, and the raw material components of the rubber materials prepared using the cobalt salts of Blank Examples 1 to 3, in parts by mass.

[0032] Table 1 Blank example 1 Blank example 2 Blank example 3 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 5# Standard Glue SCR5 100.00 100.00 100.00 100.00 100.00 100.00 100.00 100.00 100.00 100.00 Carbon Black N326 55.00 55.00 55.00 55.00 55.00 55.00 55.00 55.00 55.00 55.00 Zinc Oxide 9.30 9.30 9.30 9.30 9.30 9.30 9.30 9.30 9.30 9.30 Stearic acid 0.25 0.25 0.25 0.25 0.25 0.25 0.25 0.25 0.25 0.25 Antioxidant 4020 1.80 1.80 1.80 1.80 1.80 1.80 1.80 1.80 1.80 1.80 Antioxidant RD 0.50 0.50 0.50 0.50 0.50 0.50 0.50 0.50 0.50 0.50 RA65 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 Anti-scorch agent CTP 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 Insoluble Sulfur IS7020 5.95 5.95 5.95 5.95 5.95 5.95 5.95 5.95 5.95 5.95 Accelerator DZ 0.65 0.65 0.65 0.65 0.65 0.65 0.65 0.65 0.65 0.65 Cobalt stearate 2.50 / / / / / / / / / Cobalt neodecanoate / 1.50 / / / / / / / / Cobalt boroacylate / / 1.05 / / / / / / / Bio-based cobalt salts with resin properties / / / 2.85 2.85 2.85 2.85 2.85 2.85 2.85 .

[0033] Table 2 shows the mechanical property test and vulcanization performance test data of the rubber materials prepared by the bio-based cobalt salts with resin properties prepared by Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 and the rubber materials prepared by the cobalt salts of Blank Examples 1 to 3 according to the national standards GB / T329-2008, GB / T328-2009 and GB / T16584, wherein the rubber physical property sample preparation and vulcanization conditions are: 150°C*30min, and the rheological temperature is 150°C*60min.

[0034] Table 2 Test items Blank example 1 Blank example 2 Blank example 3 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 T10 / min:s 1:24 1:23 1:22 1:24 1:24 1:24 1:22 1:23 1:23 1:22 T90 / min:s 8:45 8:55 8:56 8:42 8:42 8:44 8:57 8:53 8:54 8:56 Tensile strength / Mpa 19.6 20.1 19.8 21.6 21.8 21.8 21.3 20.8 21.2 10.8 Elongation at break % 528 533 530 540 544 543 538 535 532 108 300% tensile stress / Mpa 12.2 12.5 12.7 12.1 12.4 12.2 12.3 12.5 10.8 4.35 Tear strength / KN / m 45 45 44 50 51 50 48 49 42 28 .

[0035] Table 3 shows the test data of the rubber materials prepared by the bio-based cobalt salts with resin properties prepared by Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 and the rubber materials prepared by the cobalt salts of Blank Examples 1 to 3, and the test data of the extraction force test and the thermal oxidation aging (105°C for 3 days), salt water aging (5% NaCl solution for 7 days), and wet heat aging (93°C*95RH% for 7 days) according to the national standard GB-T 16586-1996, initial vulcanization conditions: 150°C*30min, steel cord specifications: 3*0.20+6*0.35NT.

[0036] Table 3 Grouping performance Blank example 1 Blank example 2 Blank example 3 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Initial bonding Bonding N 740 742 749 755 756 760 752 754 761 578 Initial bonding Glue % 90 90 90 91 90 90 90 90 90 81 Thermal Oxidative Aging Bonding N 573 599 604 655 652 640 622 618 639 374 Salt water aging Glue % 80 82 85 88 90 88 86 86 88 65 Salt water aging Bonding N 512 522 555 586 590 591 568 565 579 336 Salt water aging Glue % 70 70 80 80 82 82 80 80 80 62 Damp heat aging Bonding N 579 580 595 619 623 625 609 606 599 348 Damp heat aging Glue % 81 85 86 88 89 88 87 86 86 63 .

[0037] From Tables 1 to 3, it can be found that the rubber material prepared from the bio-based cobalt salt with resin properties obtained in the embodiment has better rubber attachment rate, extraction force, hot air aging performance and salt water aging performance after vulcanization with the steel cord, and has excellent comprehensive mechanical properties, indicating that the resin mixed cobalt salt prepared by the present invention has good adhesion promotion and antioxidant effects between metal and rubber, and improves various properties of rubber.

[0038] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A bio-based cobalt salt having resin properties, characterized in that: The raw material components include, by weight: 15 to 30 parts of a first plant-based acid, 10 to 25 parts of a second plant-based acid, 15 to 35 parts of a cobalt source, 25 to 35 parts of a solvent, and 5 to 10 parts of a plant adjuvant; the first plant-based acid contains a phenolic hydroxyl structure.

2. The bio-based cobalt salt with resin properties according to claim 1, characterized in that: The first plant-based acid is vanillic acid.

3. The bio-based cobalt salt with resin properties according to claim 1, characterized in that: The second plant-based acid is coumaric acid.

4. The bio-based cobalt salt with resin properties according to claim 1, characterized in that: The cobalt source is industrial cobalt hydroxide with a cobalt content of ≥61.5%.

5. The bio-based cobalt salt with resin properties according to claim 1, characterized in that: The solvent is dimethyl carbonate.

6. The bio-based cobalt salt with resin properties according to claim 1, characterized in that: The plant auxiliary agent adopts plant microcrystalline cellulose.

7. A method for preparing a bio-based cobalt salt having resin properties, characterized in that: The method comprises the following preparation steps: (1) Weighing and setting aside the raw material components according to the raw material components and weight proportions of the bio-based cobalt salt with resin properties according to any one of claims 1 to 6; (2) The solvent, the first plant-based acid, and the second plant-based acid weighed in step (1) are added to the reactor in sequence, followed by a first stage of heating and stirring, followed by adding a cobalt source and stirring for 5 minutes, followed by a second stage of heating, followed by reflux at a temperature of 1 to 1.5 hours; then a third stage of heating is performed, followed by distillation under negative pressure for 1 to 3 hours, followed by adding a plant adjuvant, stirring for 0.5 hours, and then discharging and granulating to obtain a bio-based cobalt salt having resin properties.

8. The method for preparing a bio-based cobalt salt having resin properties according to claim 7, characterized in that: The first stage of heating is to raise the temperature to 100-120°C.

9. The method for preparing a bio-based cobalt salt having resin properties according to claim 7, characterized in that: The second stage of heating is to raise the temperature to 150-160°C.

10. The method for preparing a bio-based cobalt salt having resin properties according to claim 7, characterized in that: The three-stage temperature increase is to increase the temperature to 200-240° C.; the negative pressure is ≤-0.085 MPa.